DIABETIC KETOACIDOSIS CHARACTERISTICS AND DIFFERENCES IN TYPE 1 VERSUS TYPE 2 DIABETES PATIENTS - Rashid, Muhammad Owais; Sheikh, Aisha; Salam, Abdus; Farooq, Saad; Kiran, Zareen; Islam, Najmul (Journal of Ayub Medical College Abbottabad, 2017)
Background: Diabetes is undoubtedly one of the most challenging health problems of the 21st century. It is well known that diabetes once develop can lead to several complications. Diabetic ketoacidosis (DKA) is one of the life-threatening complications of diabetes. This study was designed to determine the frequency of DKA in diabetes patients and find out the clinical and biochemical determinants of DKA. Methods: This descriptive study was conducted at Aga Khan University Hospital (AKUH) Karachi, Pakistan from January 2010 to February 2016. All known or newly diagnosed diabetic patients of >16 years of age irrespective of gender and type of diabetes were included. Information regarding patient’s demographics, presenting symptoms, precipitating causes of DKA, biochemical profiles and outcome at the time of discharge was collected. Results: Majority (54.7%) had moderate and 12.4% had severe DKA at presentation. Previous history of DKA was found higher in type 1 diabetes patients (T1DM) (14%) as compare to (4%) type 2 diabetes patients (T2DM) (p<0.05). DKA severity was observed more (12%) in newly diagnosed (T1DM) (p<0.05). Comorbidities were found more (81%) in (T2DM) (p<0.05) Mortality was also observed higher in Type 2 diabetes patients (p<0.05). Conclusion: Majority of the diabetics had moderate to severe DKA at presentation. Mortality and morbidity related with DKA was found considerably higher among patients with T2DM while infection, myocardial infarction and stroke found as triggering factors in these patients. Keywords: Diabetic ketoacidosis (DKA); T1DM; T2DM